Amelioration of drought effects in wheat and cucumber by the combined application of super absorbent polymer and potential biofertilizer - Li,Yongbin; Shi,Haowen; Zhang,Haowei; Chen,Sanfeng (PeerJ, 2019)
Biofertilizer is a good substitute for chemical fertilizer in sustainable agriculture, but its effects are often hindered by drought stress. Super absorbent polymer (SAP), showing good capacity of water absorption and retention, can increase soil moisture. However, limited information is available about the efficiency of biofertilizer amended with SAP. This study was conducted to investigate the effects of synergistic application of SAP and biofertilizers (Paenibacillus beijingensis BJ-18 and Bacillus sp. L-56) on plant growth, including wheat and cucumber. Potted soil was treated with different fertilizer combinations (SAP, BJ-18 biofertilizer, L-56 biofertilizer, BJ-18 + SAP, L-56 + SAP), and pot experiment was carried out to explore its effects on viability of inoculants, seed germination rate, plant physiological and biochemical parameters, and expression pattern of stress-related genes under drought condition. At day 29 after sowing, the highest viability of strain P. beijingensis BJ-18 (264 copies ng−1 gDNA) was observed in BJ-18 + SAP treatment group of wheat rhizosphere soil, while that of strain Bacillus sp. L-56 (331 copies ng−1 gDNA) was observed in the L-56 + SAP treatment group of cucumber rhizosphere soil. In addition, both biofertilizers amended with SAP could promote germination rate of seeds (wheat and cucumber), plant growth, soil fertility (urease, sucrose, and dehydrogenase activities). Quantitative real-time PCR analysis showed that biofertilizer + SAP significantly down-regulated the expression levels of genes involved in ROS scavenging (TaCAT, CsCAT, TaAPX, and CsAPX2), ethylene biosynthesis (TaACO2, CsACO1, and CsACS1), stress response (TaDHN3, TaLEA, and CsLEA11), salicylic acid (TaPR1-1a and CsPR1-1a), and transcription activation (TaNAC2D and CsNAC35) in plants under drought stress. These results suggest that SAP addition in biofertilizer is a good tactic for enhancing the efficiency of biofertilizer, which is beneficial for plants in response to drought stress. To the best of our knowledge, this is the first report about the effect of synergistic use of biofertilizer and SAP on plant growth under drought stress.
Keywords: Paenibacillus; Drought stress; Super absorbent polymer; Wheat; Bacillus; Biofertilizer; Cucumber